Protecting Innovation Through Patents and Trade Secrets: Evidence for Firms with a Single Innovation - Dirk Crass; Francisco Garcia Valero; Francesco Pitton; Christian Rammer (International Journal of the Economics of Business, 2019)
This paper analyzes the use and effectiveness of patents and trade secrets designed to protect innovation. While previous studies have usually considered patents and trade secrets as substitutes for one another, we investigate to what extent and in what situations the two protection methods are used jointly. We identify protection strategies for single innovation firms and hence overcome the assignment problem of existing empirical studies, that is, whether firms using both protection methods do so for the same innovation or for different innovations. Employing firm panel data from Germany, we find fairly few differences between the determinants for choosing secrecy and patenting. Single innovators that combine both strategies, 39% of the group, tend to aim at a higher level of innovation and act in a more uncertain technological environment. Firms combining both protection methods yield significantly higher sales with new-to-market innovations, providing some evidence for a complementarity of the two protection methods.
Keywords: O31; O32; O34; 330; Patents; trade secrets; single innovation; innovation output